2017
DOI: 10.1080/10942912.2017.1381706
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of phenolic profiles and antioxidant activity of walnut (Juglans sigillata Dode) green husks

Abstract: The phenolics content and antioxidant activity of walnut (Juglans sigillata Dode) green husks were analysed during different stages of development. Contents of total phenolics and total flavonoids decreased from April 25th to June 7th, then increased during June and July, and decreased again at the beginning of August. Thirteen types of phenolic compounds were identified using HPLC of which juglone had the highest content. Because of seasonal variations, the trends of different phenolic compounds were differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
6
18
0
Order By: Relevance
“…On the contrary, the relationships between antioxidants (polyphenolics, flavonoids, and Ve) and antioxidant activity have been studied extensively in previous research (Rocchetti, Chiodelli, Giuberti, & Lucini, 2018;Santos et al, 2018). We found that the content of polyphenolics was positively correlated with total flavonoids (r = .91, p < .01), which concurred with the relationship (r = .99, p < .01) in Juglans sigillata Dode reported by Shi, Zhang, Li, and Pan (2018). It was also reported that the level of flavonoids decreased with a decline in the polyphenol content during the rapid enlargement of fruit (Shi et al, 2018).…”
Section: The Inherent Relationships Of Phytochemical Components Amosupporting
confidence: 83%
“…On the contrary, the relationships between antioxidants (polyphenolics, flavonoids, and Ve) and antioxidant activity have been studied extensively in previous research (Rocchetti, Chiodelli, Giuberti, & Lucini, 2018;Santos et al, 2018). We found that the content of polyphenolics was positively correlated with total flavonoids (r = .91, p < .01), which concurred with the relationship (r = .99, p < .01) in Juglans sigillata Dode reported by Shi, Zhang, Li, and Pan (2018). It was also reported that the level of flavonoids decreased with a decline in the polyphenol content during the rapid enlargement of fruit (Shi et al, 2018).…”
Section: The Inherent Relationships Of Phytochemical Components Amosupporting
confidence: 83%
“…In large number of studies authors relied on this test when assessing antioxidant abilities of tested compounds. 10,11,23 It is known that the leaves of green walnut, 25 kernels 26 and green husks 10 had high antioxidant activity. Basically, a higher the DPPH radical-scavenging activity is associated with a lower IC 50 value.…”
Section: Antioxidant Activity Of Extracts J Nigra Leavesmentioning
confidence: 99%
“…However, previous research indicated that only about 80 % of the radical scavenging activity could be attributed to the phenolic compounds or flavonoids, signifying that other potent antioxidants are also present in the walnut leaves. 10 The future research will be addressed to the analyses of nonphenolic compounds from black walnut leaves. CONCLUSION In this work, for the first time, a statistical method based on RSM model was used to optimize the extraction of phenolic compounds from J. nigra leaves.…”
Section: Antioxidant Activity Of Extracts J Nigra Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, previous studies on walnut husk and shells with regard to antioxidant activity revealed the polyphenolic compounds in these resources [8][9][10][11]. Stampar, Solar, Hudina, Veberic and Colaric [7] reported the existence of thirteen phenolic compounds in the husk.…”
Section: Introductionmentioning
confidence: 99%